Genetic Variability of Tunisian Faba Beans (Vicia faba L.) Based on Seeds’ Morphophysical Properties as Assessed by Statistical Analysis - Khalil Khamassi; Elyes Babay; Mustapha Rouissi; Abir Dakhlaoui; Rayda Ben Ayed; Mohsen Hanana (Journal of Food Quality)
Faba bean (Vicia faba L.) is a legume crop cultivated for its nutritious seeds that are an important worldwide source of human food and feed. Seeds characterization is a prerequisite step for faba bean quality improvement. The morphophysical characterization of the seeds of twenty-four local faba bean accessions following the UPOV descriptors and the AOAC International standards was carried out and assessed with an approach based on Euclidean statistical model. “205 Bulk” was the unique accession harboring white hilum color seed which is linked to low convicine grain content. Irregular seed shape was the most observed character among the studied accessions except “Badii” displaying an elliptical seed shape; therefore, seed shape did not allow discrimination within our Tunisian germplasm. Interestingly, the physical characters of the seeds showed significant diversity between the accessions for all the measured parameters. A highly significant variability was observed for axial, length, and width dimensions of seeds, with “Memdouh” being the longest and largest seed accession, whereas “01-02” was the shortest and narrowest. Classification of the studied faba bean germplasm accessions based on morphophysical characters using clustering by Euclidean distance revealed three different groups. Moreover, multivariate PCA analysis further classified the faba bean accessions into four main clusters. Correlation study performed by using Spearman’s test established positive correlations within physical parameters of seeds such as between mean length and mean width of seeds. Therefore, using morphophysical parameters screening, valuable phenotypes have been selected for deeper physiological characterization and further breeding programs.